"Rentabilidad de la renovación del cultivo de rosas )rosa sp.) variedad santa Ana de la empresa Sedafy floral en la zona deTabacundo". - Carrilllo Pabon, Alexandra Yeseña (2014)
Roses have experienced high growth in recent years within the Ecuadorian economy, rising to become the third largest category of non-oil exports are an important source of employment for the country His leadership has established mainly due to improved varieties, extending the offer throughout the year and its growing demand and best price getting higher returns. This research was conducted in the flower “Sedafy Floral” family business dedicated to the production and export of cut roses, located in the Tabacundo, Canton Pedro Moncayo, Pichincha Province, 50 minutes from the city of Quito, near Mojanda gaps. This area offers the best climatic conditions for the cultivation of Ecuador roses The facilities cover an area of 2.5 hectares, including 2 acres of greenhouses and 0.5 hectares for offices, water reservoir, postharvest, cold room, irrigation, bathroom, dining room, dressing rooms, green and recreational area. Its main consumer markets are Russia, Europe, America and Asia as an alternative market (Kuwait) The results obtained in this research allowed to follow the right path, saving resources, in order to achieve the objectives as are , know the costs , determine profitability , and identify possible strings of alternative marketing influencing renovation rose cultivation with improved variety (Santa Ana) company " SEDAFY FLORAL" . The economic analysis was performed through the implementation costs from greenhouse to marketing. The cost / benefit and cost to the renewal of varieties in growing roses the flower business “Sedafy Floral” where it is determined that the investment is profitable and sustainable relationship was also calculated.